GLACIOLOGICAL RESEARCH PROGRAM IN EAST QUEEN MAUD LAND, EAST ANTARCTICA PART 5, 1985 - AGETA, Yutaka; KIKUCHI, Tokio; KAMIYAMA, Kokichi; OKUHIRA, Fumio (National Institute of Polar Research, 1987)
P(論文) departmental bulletin paper